State and Society in Modern Rangoon. - Seekins, Donald M. (Asia's transformations., 2014)
While most of Asia's major cities are increasingly homogenized by rapid economic growth and cultural globalization, Rangoon, which is Burma's former capital and largest city, still bears the imprint of a unique and often turbulent history. It is the site of the Shwedagon Pagoda, a focus of Buddhist pilgrimage and devotion since the early second millennium C.E. that continues to play a major role in national life. In 1852, the British occupied Rangoon and made it their colonial capital, building a modern port and administrative center based on western designs. It became the capital of independe.